Ichthyosiform sarcoidosis: Report of a case and comprehensive review of the literature. (30th April 2021) - Chen, Henry W.; Vandergriff, Travis
Abstract: Sarcoidosis is a disease that can affect a multitude of organs and manifest as cutaneous disease. Cutaneous manifestations of sarcoidosis vary widely in morphology, earning the nickname of "great imitator, " and the diagnosis often requires clinicopathologic correlation and additional laboratory and radiographic workup. We present the case of a 42‐year‐old African American woman with ichthyosiform sarcoidosis on the bilateral lower extremities. As one of the rarest specific variants of cutaneous sarcoidosis, ichthyosiform is understudied and has been primarily documented in case reports and series. We undertake a comprehensive review of the literature to identify key clinicopathologic features including the characterization of sites of cutaneous and systemic involvement, as well as typical histopathological findings. Lower extremities were the most involved body site (85.7%). Extracutaneous organ involvement centered around pulmonary (65.7%), lymph node (57.1%), and ocular (31.4%) involvement. Of the histopathological features reported, hyperkeratosis (51.4%) and diminished stratum granulosum (62.9%) were most frequently reported in conjunction with dermal granulomas (100%). We hope that these findings will serve to aid clinicopathological correlation and accurate diagnosis of ichthyosiform sarcoidosis.